Relationships with father and mother, self-esteem and academic achievement amongst college students - Baharudin, Rozumah; Zulkefly, Nor Sheereen (EuroJournals Publishing, 2009)
The study investigates the quality of relationships between college students and their mothers and fathers, and its correlates with their self-esteem and academic achievement. A sample of 386 on-campus students of Universiti Putra Malaysia, who were identified via cluster sampling, completed a self-administered questionnaire. Results showed that generally the students had good quality relationships with their mothers(adjusted mean=3.78/5.00) and fathers (adjusted mean=3.67/5.00). Girls seemed to report better relationships with both parents compared to boys. The students rated themselves as having high level of self-esteem (adjusted mean=2.99/4.00) but, moderate in academic achievement (M=3.10/4.00). Female and male students did not show any significant difference in self-esteem; however females outperformed their male counterparts in academic. Further analysis showed that the quality of parent-students relationship was positively and significantly related to self-esteem and academic achievement. Students with good quality relationship with their parents evaluated themselves positively compared to others. Nonetheless, only those with good relationships with their mothers rather than their fathers showed good performance in school. The present study adds to the body of knowledge on the impacts of parental relationships on the adolescents’ outcomes.